Subacute cardiac toxicity following autologous haematopoietic stem cell transplantation in patients with normal cardiac function. Issue 7 (10th December 2007) - Chung, T; Lim, W-C; Sy, R; Cunningham, I; Trotman, J; Kritharides, L
Abstract : Objective: To investigate subacute cardiac toxicity in patients with normal baseline cardiac function following autologous haematopoietic stem cell transplantation. Design: Prospective observational study. Patient and methods: Thirty-two consecutive patients (mean (SD) age 60 (11) years) with normal left ventricular ejection fraction (LVEF ⩾50%) undergoing autologous haematopoietic stem cell transplantation were studied. Transthoracic echocardiography (including colour tissue Doppler imaging-derived myocardial velocities, strain and strain rates), troponin-T and B-type natriuretic peptide (BNP) and clinical details were recorded at baseline, after conditioning chemotherapy and serially over 6 weeks from the day of transplantation. Results: The mean (SD) LVEF at baseline was 62 (6)% and decreased to 55 (16)%, 6 weeks after transplantation (p = 0.007). Cardiac toxicity (⩾10% absolute decline of LVEF to an LVEF ⩽50%) developed in 10 (31%) patients within 17 (8) days of transplantation and was usually reversible. In these 10 patients, the nadir LVEF was 39 (12)%. Two patients developed severe clinical pulmonary oedema, one episode of which was fatal. Troponin-T was mildly raised in only three of the patients with cardiac toxicity. Peak BNP values were similar in patients with or without post-transplant cardiac toxicity (149 (100) vs 196 (178) pg/ml, p = 0.43). Multivariate Cox proportional hazard regression identified baseline mitral annular systolic velocity as the only independent predictor of cardiac toxicity (hazard ratio 0.42, 95% confidence interval 0.20 to 0.86, p = 0.02). Conclusion: Subacute cardiac toxicity is common after autologous haematopoietic stem cell transplantation, even in patients with apparently normal left ventricular function. Anticipation of the period of greatest risk and recognition of patients with subclinical myocardial dysfunction may prevent clinical heart failure.